Investigating the role of specific inflammasome components during inflammatory disease - KENEALY, SINEAD (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2019)
Inflammasomes are multi-protein complexes that act as intracellular innate immune receptors. The first inflammasome was initially defined by Martinon et al in 2002 and 16 years on, this increasingly explored area has led to the identification of over 10 different inflammasomes that recognise and respond to a variety of ligands. More recent evidence has linked polymorphisms in inflammasome components to autoinflammatory syndromes and diseases. The majority of autoinflammatory syndromes are in fact linked to mutations in inflammasome components. Examples include mutations in NLRP3, Pyrin, and NLRP12 resulting in disorders such as Cryopyrin-Associated periodic Syndromes (CAPS), Familial Mediterranean Fever (FMF) and CAPS-like syndrome, respectively. This study explores novel aspects of inflammatory regulation in the context of two inflammation-associated diseases, an experimental murine model of psoriasis, and an autoinflammatory syndrome. Psoriasis is an inflammatory-mediated disease that was previously believed to be driven by an adaptive immune response. However, more recent evidence suggests a contribution of both innate and adaptive immune cells to the pathogenesis of psoriasis. Expression of caspase-4 and 5, mediators of the non-canonical inflammasome, are reported to be increased in human psoriatic lesions. This study investigates the role of caspase-11, the murine ortholog of human caspases-4 and -5, in mediating psoriasis. Findings from this study reveal that when compared to wild-type mice, caspase-11 deficient mice are significantly protected from the symptoms arising from Imiquimod-induced psoriasis. Decreased angiogenic markers, proliferation and epidermal thickening were observed in the skin of caspase-11 deficient mice. Decreased infiltration of leukocytes to the skin and decreased pyroptosis were also observed in Casp-11-/- skin, which may explain the absence of psoriasis in these mice. We propose that non-canonical inflammasome mediated inflammation is responsible for driving the pathogenesis of psoriasis. Findings from this study identify the inflammatory caspase, caspase-11 as a potential drug target for the treatment of this disease. A clinical collaboration established with Our Lady?s Children?s Hospital, Crumlin has identified a novel mutation in NLRP6 as a causative agent of a previously undiscovered autoinflammatory syndrome. Our findings suggest that a patient presenting with Blau-like autoinflammatory symptoms has a rare loss-of-function NLRP6R653G mutation, which is responsible for the patient?s sustained inflammatory symptoms. This study characterises the patient?s immune responses to a range of inflammatory stimuli and inflammasome activators. Findings suggest that patient NLRP6R653G has consistently elevated basal IL-6 expression, dysregulated NFκB signalling and increased production of pro-IL-1β in response to LPS. In vitro evidence implicates a role for NLRP6 in mediating NFκB activation in the presence of ASC, which is abolished in the presence of the mutation. Conversely, mutation NLRP6R653G has no observable impact on inflammasome formation in vitro. Collectively, these findings suggest that the most significant impact of the NLRP6R653G mutation is on NFκB regulation. This study identifies the NLRP6 SNP as a causative gene for a novel monogenic autoinflammatory disease, which will have a significant impact on the autoinflammatory disease research field. Findings from this study also provide significant insight into the importance of NLRP6 signalling during innate immune responses, which is not well characterised at present.
APPROVED
Keywords: Autoinflammation; Inflammasomes; Psoriasis; Inflammatory caspases; NLRP6